Electron Transporting Perylene Diimide-Based Random Terpolymers with Variable Co-Monomer Feed Ratio: A Route to All-Polymer-Based Photodiodes - Aivali, Stefania; Yuan, Peisen; Panidi, Julianna; Georgiadou, Dimitra G.; Prodromakis, Themis; Kallitsis, Joannis K; Keivanidis, Panagiotis E.; Andreopoulou, Aikaterini K. (My University, 2022)
A route toward processable n-type terpolymers is presented herein based on the random donor-acceptor-donor-acceptor (D-A1)-(D-A2) molecular configuration. Carbazole is utilized as the electron donating unit (D) combined with perylene diimide (PDI) as the first electron acceptor (A1) and either one of two different benzothiadiazole (BTZ) derivatives (di-thienyl substituted-BTZ and di-3,4-ethylenedioxythienyl substituted-BTZ) as the second electron accepting unit (A2). Increasing the content of the PDI co-monomer resulted in terpolymers of higher molecular weights, enhanced solubility, and stronger n-type character. The physicochemical properties of the random PDI-Cz-BTZ derivatives are fine-tuned based on the feed ratio of the co-monomers. Photodiode devices were demonstrated, having photoactive layers composed of the rich in PDI terpolymer, namely, P4 having a 75% PDI content, and the PCE10 electron donor, under various ratios. For a range of P4 blend compositions, UV-Vis, is spectroscopy confirmed the strong absorption of the blend films across the 350-800 nm spectral region, and AFM imaging verified their low surface roughness. The study of the electro-optical device properties identified the 1:2 blending ratio as the optimum PCE10:P4 combination for maximum charge photogeneration efficiency. Despite the relatively deep LUMO energy of the n-type P4 terpolymer (ELUMO = -4.04 eV), trap-induced charge recombination losses were found to limit the PCE10:P4 photodiode performance. Unipolar devices of the P4-alone exhibited hole and electron mobility values of 2.2 × 10-4 and 6.3 × 10-5 cm2 V-1 s-1, respectively.
Keywords: Acceptor; Organic solar cells; Low bandgap polymers; Naphthalene diimide; Perylene diimide; Electron acceptor